2009
DOI: 10.1246/bcsj.82.1323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Theory Including Quantum Effects and Thermal Fluctuations

Abstract: Recent progress in our theoretical developments and applications where thermal fluctuations and quantum effects are important are reviewed. We first show that motions of a confined atom coupled with a fullerene cage cause large thermal fluctuation of the effective charge on the confined atom and that the fluctuation is sensitive to applied temperature and the number of confined species. Second, two different approaches to treat nuclear quantum effects are discussed. One is nonBornOppenheimer (NBO) molecular th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…Recently Shigeta and co-workers derived a general expression for the expectation value of an arbitrary operator by means of cumulants rather than moments [9][10][11][12][13][14][15][16][17][18][19]. For one-dimensional case, the expectation value of a differential arbitrary operator, A s ( q, p ) , that consists of the symmetric sum of power series of q and p is derived as…”
Section: Quantized Hamilton Dynamics and Quantal Cumulant Dynamicsmentioning
confidence: 99%
“…Recently Shigeta and co-workers derived a general expression for the expectation value of an arbitrary operator by means of cumulants rather than moments [9][10][11][12][13][14][15][16][17][18][19]. For one-dimensional case, the expectation value of a differential arbitrary operator, A s ( q, p ) , that consists of the symmetric sum of power series of q and p is derived as…”
Section: Quantized Hamilton Dynamics and Quantal Cumulant Dynamicsmentioning
confidence: 99%
“…According to the previous papers,26–31 we suggested that the expectation value of the operator composed of both position and momentum operators could be expressed as a function of positions, momentums, and cumulants 32, 33. Here, we also apply the same methodology to the evaluation of the total energy within a second‐order approximation.…”
Section: Theorymentioning
confidence: 99%
“…One of the quite distinguished works to treat real‐time quantum effects with lower cost is the quantized Hamilton dynamics (QHD) approach,20–25 which Prezhdo and coworkers developed based on the Heisenberg's equations of motion (EOM). Recently, we have developed a quantal cumulant mechanics (QCM), where coordinates, momenta, and cumulants are essential variables in this extended formalism of the classical mechanics toward the quantum mechanics 26–30. The key ideas are that a coordinate shift operator acting on a potential operator is introduced and that a cumulant expansion is applied to the evaluation of the expectation value of the shift operator.…”
Section: Introductionmentioning
confidence: 99%
“…Kanno et al have extended the nonadiabatic dynamics of chiral aromatic molecules, including vibronic couplings modulated by an atto‐sec linearly polarized pulse laser field. Since a full‐quantum description for many electron systems is limited to a few electron systems, such as H 2 and at most LiH, a time‐dependent density functional theory is alternatively used for the real‐time electron dynamics at fixed nuclei using real‐space density functional theory . However, it is difficult for this method to describe complex electronic structures, which requires the multiconfigurational nature of the electronic wave function.…”
Section: Introductionmentioning
confidence: 99%
“…Since a full-quantum description for many electron systems is limited to a few electron systems, such as H 2 and at most LiH, a time-dependent density functional theory is alternatively used for the real-time electron dynamics at fixed nuclei using real-space density functional theory. [10,11] However, it is difficult for this method to describe complex electronic structures, which requires the multiconfigurational nature of the electronic wave function. To address these issues, multiconfigurational electron dynamics and the time-dependent completeactive-space self-consistent field using the real-space grid basis are recently developed to investigate the ionization dynamics of small molecules in an intense laser field.…”
Section: Introductionmentioning
confidence: 99%